Pengaruh Penerapan Gaya Mengajar Latihan Terhadap Gerak Dasar Menendang Bola Dengan Kaki Bagian Dalam Pada Permainan Sepak Bola Pada Siswa SMP Negeri 1 Modayag Barat - Dandi Palima; Yuliana Sattu; Tony Pandaleke (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
This study concludes that the use of training teaching style has a significant effect on improving the basic ability to kick the ball with the inside of the foot in the soccer game of students at SMP Negeri 1 Modayag Barat. This is proven through the results of statistical analysis, where the t-count value of 8.77 exceeds the t-table of 2.074. This means that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. Before the hypothesis testing is carried out, the data is first tested to see normality using the Lilliefors method and homogeneity by comparing group variances. The results show that the data has a normal distribution and homogeneous variance, so it meets the requirements for a t-test. To measure students' abilities, an instrument is used in the form of a kicking ball skill test with the inside of the foot, with the support of facilities such as a soccer field, ball, whistle, and stationery. The study involved 24 students who were randomly divided into two groups, namely the experimental group and the control group, each consisting of 12 people. This study uses an experimental method with a Randomized Pre-Test and Post-Test Control Group Design. The formulation of the problem to be answered in this study is whether the teaching style of training can affect the improvement of basic skills in kicking the ball with the inside of the foot. The main objective of this study is to determine how far the application of the teaching style of training can help improve these basic skills in students of SMP Negeri 1 Modayag Barat